Tethered Pd-complex on solid support: catalyst for acid-free carbonylation reactions - Sarkar, Bibbas R.; Mukhopadhyay, Kausik; Chaudhari, Raghunath V. (Catalysis Communictions, 2007)
{Palladium complex [
Keywords: decomposition; direct H2O2 synthesis; halides; Promoter